The Neganthropocene - Stiegler, Bernard (CCC2 Irreversibility, 2018)
In the essays and lectures here titled Neganthropocene, Stiegler opens an entirely new front moving beyond the dead-end "banality" of the Anthropocene. Stiegler stakes out a battleplan to proceed beyond, indeed shrugging off, the fulfillment of nihilism that the era of climate chaos ushers in.